Research on green design framework and support system of metal cutting machine. (October 2019) - Wang, Xingrong; Yan, Chunping; Huang, Wei; Xu, Jianping
Abstract: In order to improve the green design level of metal cutting machine tools, the framework and implementation methods for enhancing the green performance of machine tool's design process were studied. Analysing the environmental impact of design process, studying the green key points in the design process of materials, structures, hydraulics, lubrication and cooling, a green design framework for the metal cutting machine was established. Centering on the machine tool design process; Researching on the machine tool design support technology and implementation tools, a basic support system for green design of metal cutting machine that integrates technical support layer, interaction layer, tool support layer, technical support layer and user service layer was established. The green design support system for gear making machine was developed and applied to verify the guiding role of green framework and support system in the green design process of metal cutting machine tool.